(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
The melting of methylene blue (MB) complexes of DNA with different GC-content sequences at 0.02 M ionic strength of the solution has been carried out. It was shown that the change of melting interval width of MB complexes with DNA increases depending on GC-content enhancement within DNA sequences. It was revealed that MB is bound to DNA by semi-intercalation mode.